Diagnostic efficacy of metagenomic next generation sequencing in bronchoalveolar lavage fluid for proven invasive pulmonary aspergillosis - Jia, Hongxia; Liu, Hongping; Tu, Meng; Wang, Yan; Wang, Xinjuan; Li, Jing; Zhang, Guojun (Frontiers in Cellular and Infection Microbiology, 2023)
Objective To assess the diagnostic efficacy of metagenomic next generation sequencing (mNGS) for proven invasive pulmonary aspergillosis (IPA). Methods A total of 190 patients including 53 patients who had been diagnosed with proven IPA were retrospectively analyzed. Using the pathological results of tissue biopsy specimens as gold standard, we ploted the receiver operating characteristic (ROC) curve to determine the optimal cut-off value of mNGS species-specific read number (SSRN) of Aspergillus in bronchoalveolar lavage fluid (BALF)for IPA. Furthermore, we evaluated optimal cut-off value of mNGS SSRN in different populations. Results The optimal cut-off value of Aspergillus mNGS SSRN in BALF for IPA diagnosis was 2.5 for the whole suspected IPA population, and 1 and 4.5 for immunocompromised and diabetic patients, respectively. The accuracy of mNGS was 80.5%, 73.7% and 85.3% for the whole population, immunocompromised and diabetic patients, respectively. Conclusions The mNGS in BALF has a high diagnostic efficacy for proven IPA, superioring to Aspergillus culture in sputum and BALF and GM test in blood and BALF. However, the cut-off value of SSRN should be adjusted when in different population.